Neck pain: a clinical analysis of causes and therapy priorities - G. R. Tabeeva (Неврология, нейропсихиатрия, психосоматика)
Neck pain is one of the common causes of maladjustment. Acute neck pain in most cases regresses independently in the period of a few weeks to months; however, it recurs in half of cases. Although the potential specific causes of cervicalgia are rare; nevertheless, in some cases the patient should undergo a detailed examination that is based on the identification of red flags and can optimize a search for the cause of pain syndrome. A consideration of the important principles of classifying pain in acute and chronic, neuropathic and nociceptive pain can serve as an important landmark in choosing the optimal treatment strategy for a patient. Unlike low back pain, neck pain has been investigated in an insufficient number of randomized controlled studies, which makes this analysis extremely relevant. The paper discusses the use of nonsteroidal anti-inflammatory drugs for back pain and the efficacy and safety of celecoxib.